The ancient magus' bride. Volume 2 - Yamazaki, Kore (Seven Seas Entertainment, LLC, 2015)
"Great power comes at a price... Chise Hatori's life has recently undergone shocking change. As a sleigh beggy--a person capable of generating and wielding tremendous magical power--she has transformed from an unwanted child to a magician's apprentice who has been introduced to fae royalty. But Chise's newly discovered abilities also mean a cruel fate awaits her." -- Page [4] of cover.